IMPACT OF DRUG ABUSE ON THE LIVES OF YOUTH IN A SEMI-URBAN COMMUNITY SETTING IN NIGERIA - Faronbi, Joel Olayiwola (Journal of Community and Health Sciences, 2020)
This study examined involvement in drug abuse and its associated consequences among secondary school students in Nigeria. A structured questionnaire was used to collect data from 160 Secondary School students selected using a multi-stage sampling technique. Results showed that 85% of the respondents had a high level of awareness of drug abuse and 48.1% were involved in drug abuse. This study also revealed that friends, peer groups and involvement in social group were some of the factors influencing youths' participation in drug abuse. A significant relationship exists between respondents' involvement in drug abuse and health conditions (X = 53.53) and academic performance (X = 6.727). This study concludes that involvements in drug abuse have a negative impact on the lives of the youth. Therefore, multidisciplinary actions should be put in place to end drug abuse among the youths in our community.